1978
DOI: 10.1111/j.1095-8649.1978.tb03475.x
|View full text |Cite
|
Sign up to set email alerts
|

Particulate and filter feeding in threadfin shad, Dorosoma petenense, at different light intensities

Abstract: Previous workers inferred from stomach analyses that threadfin shad (Dorosomapetenense) ate plankton by both filter and particulate feeding. These inferences were confirmed in this study by laboratory experiments in which both types of feeding were observed. Threadfin shad consumed relatively small food particles ( < 0.39 mm) by filtration, while larger prey (7.5 mm) were eaten individually. The shad were able to filter feed on small foods (brine shrimp nauplii and phytoplankton) at all light intensities from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 7 publications
(14 reference statements)
0
27
0
Order By: Relevance
“…Previous laboratory work on planktivorous fish had shown that feeding behaviour and rate of food consumption were dependent on size and density of available prey (Leong & O'Connell 1969, O'Connell 1972, O'Connell & Zweifel1972, Durbin & Durbin 1975, Janssen 1976, Holanov & Tash 1978, Hunter & Dorr 1982, Gibson & Ezzi 1985. General conclusions drawn from these studies are that feeding is selective and planktivores can have a marked impact upon their prey communities.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous laboratory work on planktivorous fish had shown that feeding behaviour and rate of food consumption were dependent on size and density of available prey (Leong & O'Connell 1969, O'Connell 1972, O'Connell & Zweifel1972, Durbin & Durbin 1975, Janssen 1976, Holanov & Tash 1978, Hunter & Dorr 1982, Gibson & Ezzi 1985. General conclusions drawn from these studies are that feeding is selective and planktivores can have a marked impact upon their prey communities.…”
Section: Introductionmentioning
confidence: 52%
“…Observations during the collection of the reactive distance data indicated that the anchovy formed a search image for a prey type that was offered several times in succession, but there are no data about the length of time such an image persists. (Janssen 1976(Janssen , 1978, Dorosoma petenense (Holanov & Tash 1978) and Clupea harengus (Gibson & Ezzi 1985). The major difference in the feeding behaviour of E. capensis was that they did not filter feed on large particles when present in high densities nor switch to biting when the density was reduced below a threshold concentration as described for other planktivores (O'Connell 1972, O'Connell & Zweifel 1972, Hunter & Dorr 1982, Gibson & Ezzi 1985.…”
Section: Particulate Feedingmentioning
confidence: 99%
“…A similarly rapid decrease in foraging efficiency over the same range of light intensities has been noted for other species of fish feeding on planktonic prey (e.g. Minnow Phoxinus phoxinus (Harden Jones 1956), Coho Salmon Oncorhynchus kisutch (Brett & Groot 1963), Threadfin Shad Dorosoma petenense (Holanov & Tash 1978), Bream Abramis brama (Townsend & Risebrow 1982), Cutthroat Trout Oncorhynchus clarkii and Dolly Varden Salvelinus malma (Henderson & Northcote 1985) and Herring Clupea harengus (Batty, Blaxter & Richard 1990)). The same phenomenon has also been documented for the piscivorous Largemouth Bass Micropterus salmoides (McMahon & Holanov 1995), even though it is feeding on much larger prey items.…”
Section: Discussionmentioning
confidence: 99%
“…As shad grow, their foraging strategies change from visual feeding, focusing almost exclusively on zooplankton, to a more variable diet of zooplankton, phytoplankton, and detritus (Haskell 1959, Gerdes and McConnell 1963, Baker and Schmitz 1971. When targeting zooplankton, they particulate-feed on larger taxa and filter-feed on smaller species (Brooks 1968, Holanov andTash 1978). This ability to use gill rakers to filter smaller plankton species is likely the principal mechanism by which shad decimate zooplankton communities.…”
Section: Discussionmentioning
confidence: 99%